Pengaruh Stunting terhadap Perkembangan Sosio-Emosional dan Kognitif pada Anak Usia Dini di Puskemas Alak, Kota Kupang - Maria Fatima Saga Wea; Johana Art Cindy Peny; Oklan B.T Liunokas (Lembaga Pengembangan Kinerja Dosen, 2025)
Children are the precious successors of the nation, so parents are expected to educate, protect and nurture their children to have a creative, intelligent, healthy and productive future. Aspects of development that can be affected by stunting can be clearly seen in aspects of children's cognitive and socio-emotional development. In this study, sampling of early childhood aged 24-59 months in the Alak Health Centre Area, Kupang City. Quantitative Research Method with cross sectional method research design with the results there is a significant effect of stunting on socio-emotional development because the sig value. Fisher's Exact Test 0.000 <0.05 and there is a significant effect of stunting on children's cognitive development because the sig value. Fisher's Exact Test 0.000 <0.05. In this study there is a significant influence on socio-emotional and cognitive development in children who experience stunting conditions.